Understanding Trauma in Migration: A Scoping Review of How Trauma is Conceptualized in Literature on West Asian Young Women in Western Contexts - Karami, Ronak; Collin-Vézina, Delphine (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents)

(untitled) (Canada Research Chair in Interpersonal Traumas and Resilience/Chaire de recherche du Canada sur les traumas interpersonnels et la résilience, 2024)
Objectives: Trauma in migration is shaped by individual, social, and structural factors. Using an intersectional lens, this scoping review examines how trauma (i.e., as defined by the Substance Abuse and Mental Health Services Administration; SAMHSA, 2014) is conceptualized in literature on young West Asian women in Western contexts. Given large-scale migration form West Asia over the past two decades, understanding these definitions is key to identifying gaps and informing resilience and recovery efforts.Methods: Using Arksey and O'Malley’s (2005) five-stage framework, a scoping review was conducted. From 424 articles (post-duplicates), 112 were screened, and 15 met the inclusion criteria for final analysis.Results: Trauma in migration is mainly defined as exposure to life-threatening events like war, persecution, or refugee camp conditions. Its impact is shaped by pre-existing (e.g., age, gender) and situational (e.g., discrimination, cultural dislocation) factors. Effects are typically framed clinically (e.g., post-traumatic stress disorder (PTSD), depression, anxiety, and somatization).Conclusions: Trauma is often framed as isolated events, with little attention to ongoing, complex experiences. Lived experiences and broader impacts are overlooked, with a reliance on the Diagnostic and Statistical Manual of Mental Disorders (DSM) and International Classification of Diseases (ICD) frameworks. Intersectionality and trauma specific to young West Asian migrant women is rarely addressed across all three Es of trauma: Event, Experience, and Effect. Recovery strategies lack tangible actions.Implications: Future research could explore trauma’s complex nature. Centering the lived experiences of young West Asian migrant women through intersectional and mixed-methods approaches is essential. Policies must be trauma-informed, gender- and age-responsive, and address post-migration stressors. Interventions should be co-designed with the target population, culturally grounded, and attuned to systemic and relational dimensions of trauma.